Pulmonary Arteriovenous Fistulae After Fontan Operation: Incidence, Clinical Characteristics, and Impact on All-Cause Mortality - Ohuchi, Hideo; Mori, Aki; Nakai, Michikazu; Fujimoto, Kazuto; Iwasa, Toru; Sakaguchi, Heima; Kurosaki, Kenichi; Shiraishi, Isao (Frontiers in Pediatrics, 2022)
Background: The Fontan operation is a surgical procedure used in children with univentricular hearts. Pulmonary arteriovenous fistulae (PAVF) is one of the major complications after a Fontan operation. However, the incidence and related clinical pathophysiology of PAVF remain unclear. Purpose: This study aimed to clarify PAVF incidence, clinical characteristics, and its influence on all-cause mortality. Methods and Results: We serially assessed the presence of PAVF using pulmonary artery angiography and/or contrast echocardiography during catheterization in 391 consecutive Fontan patients and compared the results with the Fontan pathophysiology and all-cause mortality. PAVF developed in 36 patients (9.2%) included 30 diffuse- and 6 discrete-PAVF types. PAVF-free rate at 1, 5, 10, 15, 20, and ≥ 25 years after Fontan operation was 97%, 96%, 93%, 88%, 87%, and 83%, respectively. The mean arterial blood oxygen saturation (SaO2) in those with diffuse-PAVF at each corresponding postoperative stage was 90%, 91%, 91%, 91%, 89%, and 88%, respectively, showing lower SaO2 than that in the non-PAVF patients (p < 0.01 for all). However, there was no difference in SaO2 between the patients with discrete-PAVF and those without PAVF. During a median follow-up of 2.9 years, 31 patients, including 12 PAVF patients, died. PAVF patients had a higher mortality rate (p = 0.01), especially those with diffuse-PAVF, than those without PAVF (hazard ratio: 3.6, 95% confidence interval: 1.6–7.8, p = 0.0026). Conclusions: Patients who underwent Fontan surgery had an increasing incidence of PAVF as they aged. Discrete-PAVF had no influence on SaO2 or mortality, whereas a presence of diffuse-PAVF caused hypoxia and had an adverse impact on all-cause mortality.